Warmer winters are associated with lower levels of the cryoprotectant glycerol, a slower decrease in vitellogenin expression and reduced virus infections in winter honeybees. (January 2022) - Prado, Alberto; Brunet, Jean-Luc; Peruzzi, Mathilde; Bonnet, Marc; Bordier, Celia; Crauser, Didier; Le Conte, Yves; Alaux, Cedric
Graphical abstract: Highlights: We analyzed how warmer winters affect honeybee overwintering physiology. Warmer winters are associated with lower levels of the cryoprotectant glycerol. The expression levels of antioxidant genes were not affected by winter conditions. A slower decrease in apidaecin and vitellogenin was found under warmer winters. The decline in viral infection levels was more pronounced under warmer winters. Abstract: Within the context of climate change, winter temperatures at high latitudes are predicted to rise faster than summer temperatures. This phenomenon is expected to negatively affect the diapause performance and survival of insects, since they largely rely on low temperatures to lower their metabolism and preserve energy. However, some insects like honeybees, remain relatively active during the winter and elevate their metabolic rate to produce endothermic heat when temperatures drop. Warming winters are thus expected to improve overwintering performance of honeybees. In order to verify this hypothesis, for two consecutive years, we exposed honeybee colonies to either a mild or cold winter. We then monitored the influence of wintering conditions on several parameters of honeybee overwintering physiology, such as levels of the cryoprotectant glycerol, expression levels of immune and antioxidant genes, and genes encoding multifunctional proteins, including vitellogenin, which promotes bee longevity. Winter conditions had no effect on the expression of antioxidant genes, and genes related to immunity were not consistently affected. However, mild winters were consistently associated with a lower investment in glycerol synthesis and a higher expression of fat body genes, especially apidaecin and vitellogenin. Finally, while we found that viral loads generally decreased through the winter, this trend was more pronounced under mild winter conditions. In conclusion, and without considering how warming temperatures might affect other aspects of honeybee biology before overwintering, our data suggest that warming temperatures will likely benefit honeybee vitality by notably reducing their viral loads over the winter.